2021
DOI: 10.1101/2021.04.17.440269
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adipose gene expression profiles reveal novel insights into the adaptation of northern Eurasian semi-domestic reindeer (Rangifer tarandus)

Abstract: Reindeer (Rangifer tarandus) are semi-domesticated animals adapted to the challenging arctic conditions of northern Eurasia. Adipose tissues play a crucial role in animals living in northern environments by altering gene expression in their tissues to regulate energy homeostasis and thermogenic activity. Here, we performed transcriptome profiling by RNA sequencing of adipose tissues from three different anatomical depots: metacarpal (bone marrow), perirenal, and prescapular fat in Finnish and Even reindeer (in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 83 publications
2
6
0
Order By: Relevance
“…For some genes, we found additional evidence in species phylogenetically close to cattle. For example, according to Swain and colleagues, variations in TMBIM6 affect the rectal temperature in Indian goats [48], while FKBP11 is a candidate for involvement in seasonal adaptations in reindeer (Rangifer tarandus) [49]. There are several genes that are related to thermoregulation or cold adaptation in non-ungulate species.…”
Section: Discussionmentioning
confidence: 99%
“…For some genes, we found additional evidence in species phylogenetically close to cattle. For example, according to Swain and colleagues, variations in TMBIM6 affect the rectal temperature in Indian goats [48], while FKBP11 is a candidate for involvement in seasonal adaptations in reindeer (Rangifer tarandus) [49]. There are several genes that are related to thermoregulation or cold adaptation in non-ungulate species.…”
Section: Discussionmentioning
confidence: 99%
“…White adipose tissue stores energy, whereas brown adipose tissue dissipates stored energy as heat by burning fatty acids to maintain body temperature [9]. Fat in bone marrow acts as an energy reservoir contributing to metabolic processes and undergoes dynamic changes, for example, as a result of starvation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Fat in bone marrow acts as an energy reservoir contributing to metabolic processes and undergoes dynamic changes, for example, as a result of starvation [10]. Weldenegodguad et al [9] recently reported that the gene expression profiles of metacarpal tissues were distinct from those of perirenal and prescapular fats in semi-domestic reindeer (Rangifer tarandus), providing interesting insights into the nature of adipose tissues, with candidate genes involved in immune response and energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations